Histology and Raman spectroscopy of limed human remains from the Rwandan Genocide. (February 2020) - Schotsmans, Eline M.J.; Wessling, Roland; McClue, W. Alan; Wilson, Andrew S.; Edwards, Howell G.M.; Denton, John
Abstract: The Murambi Genocide Memorial Centre is one of the major centres in Rwanda that commemorate the 1994 Rwandan genocide. Seventeen months after the genocide, about 1000 excavated human remains were put on display in Murambi Technical School. Repeated efforts were made to desiccate the human remains with lime for educational reasons. The aim of this study was to assess their state of preservation and understand the extent of degradation of the tissue. Limed soft tissue samples from four individuals were examined with light and electron microscopy, and subjected to histological analysis. Raman spectroscopy at 785 nm and 1064 nm provided information about the impact of environmental conditions on the extent of deterioration to these samples, the presence of organics and the conversion of the associated lime from calcium hydroxide to calcium carbonate. While visual degradation of the bodies in Murambi has been reported, this study confirms deterioration at a microscopic and molecular level. Both histology and Raman spectroscopic analysis revealed that the limed bodies in Murambi were deteriorating at the time the samples were collected. The results of this study will inform future decisions regarding the long-term conservation of those human remains. Highlights: Displayed human remains from the Rwandan Genocide showed ongoing deterioration. Histological analysis revealed deterioration on a microscopic level. Only collagen survived after 16 years of death and display, as observed by histological analysis. Raman spectroscopy demonstrated molecular deterioration. Liming the remains did not stop biodeterioration.